Pengaruh Kemandirian, Efektifitas Pendapatan Asli Daerah dan Belanja Daerah terhadap Kinerja Keuangan Daerah - Dessy Ari Permatasari; Sri Trisnaningsih (Universitas Batanghari Jambi, 2022)
This study aims to examine and analyze the effect of independence, effectiveness of local revenue and regional expenditures on regional financial performance at the Regional Financial and Asset Management Agency of East Java Province (BPKAD). This research is quantitative in nature with the type of data in the form of documentary data. The population used in this study were all regencies and cities in East Java Province which consisted of 9 cities and 29 regencies contained in the Regional Financial and Asset Management Agency of East Java Province (BPKAD) with an observation period in 2014-2018. The sampling technique in this research is purposive sampling technique with a sample of 190 data. This study was analyzed by simple linear regression using the SPSS program. The results of this study indicate that Regional Independence, Effectiveness of Regional Revenue, and Regional Expenditures have a positive effect on Regional Financial Performance.